Unveiling Overclaiming in User-Generated Content: How It Affects Consumer Trust and Impacts Educational Approaches to Digital Literacy - Putri, Liestyaningrum Rahmadhani Wisnu; Sutrisno; Sani, Della Tiara (Al-Qalam Institue, 2025)
This study examines the influence of user-generated content (UGC) authenticity on purchase intention, with consumer trust serving as a mediating variable, and draws parallels to educational management, particularly in digital learning environments. The research highlights how the phenomenon of overclaiming in UGC, especially on platforms like TikTok, raises concerns about authenticity, similar to challenges faced by educational institutions in ensuring the credibility of online content. Using a survey of 103 TikTok users, the study finds that UGC authenticity has a positive influence on consumer trust, which in turn significantly impacts purchase intention. These findings underscore the importance of maintaining authenticity and transparency in content, not only in marketing but also in educational settings, where trust in content is crucial for student engagement, motivation, and academic success. This study provides implications for the importance of authenticity and transparency in digital content in educational management. To increase student trust and engagement, educators must manage authentic information on digital platforms. Additionally, digital curricula should prioritize the development of critical thinking skills and information ethics in students.